Why Do Heterogeneous Outcomes Emerge in Urban Village Redevelopment? A Comparative Study of Four Cases in China - Dinghuan Yuan; Haijun Bao; Yung Yau; Yancun Lin (Land)
Successfully advancing the redevelopment of urban villages can unlock land resources for high-quality urban development. This study attempts to explain the heterogeneous outcomes of urban village redevelopment projects in China. A comparative case study method is adopted to analyze the transaction costs and the processes applied under distinct institutional arrangements. The analysis of four cases demonstrates how institutional arrangements affect transaction costs by creating a power structure that encompasses the different participants, who represent the different interests of constituent groups in exchanges of land and housing. This study demonstrates that institutional arrangements are not immutable. In addition to transaction costs, changes in the external institutional environment can alter institutional arrangements. Changes in relative prices and ideologies can also induce institutional changes. Subtle factors, such as issues indirectly linked to the redevelopment, can increase the transaction costs of achieving a consensus if policymakers ignore them in the initial policymaking stage. The findings contribute to a nuanced understanding of the heterogeneous outcomes of urban village redevelopment in China and will encourage local governments to take effective measures to ensure smooth urban village redevelopment.